(untitled) (Global Scientific Review, 2023)
This article highlights the questions of people who, under certain conditions, were forced to leave their homes in the Middle East and move to other countries. The problems faced by these groups of people are highlighted. It also highlights the work of the UN and other international organizations in order to provide refugees with basic necessities. This article discusses how, along with the political dialogue on the fate of the Palestinian refugees, lined up the work of the UN on providing direct assistance to the Palestinians. The article traces the work of the Conciliation Commission, the United Nations Relief for Palestine Refugees, and the reasons for the creation of the Near East Relief and Works Agency for Palestine Refugees. At the end of the article, some recommendations are given for further studying this problem and resolving the problems that refugees face in a new society.